A case of Young Stroke due to Moyamoya Disease - Razzak, Md Abdur; Kawnayn, Ghulam; Naznin, Fateha; Rahman, Quazi Audry Arafat (Journal of Armed Forces Medical College, Bangladesh, 2020)
Moyamoya disease is a disease in which certain arteries in the brain are constricted. Blood flow is blocked by the constriction, and also by blood clots (thrombosis). A collateral circulation develops around the blocked vessels to compensate for the blockage, but the collateral vessels are small, weak, and prone to bleeding, aneurysm and thrombosis which may result in TIA, recurrent ischemic or hemorrhagic stroke or seizure. The disease may manifest in pediatric age or young adults. In May 2019 we have diagnosed a young lady with Moyamoya disease who presented with right sided hemiplegia, motor aphasia and dysphagia. She was labeled as hypertensive 6 months prior to this event and used to take anti-hypertensive irregularly and gave past history of occasional headache. Her CT scan and MRI of brain revealed left sided ischemic infarct involving frontotemporoparietal region and cerebral angiogram revealed narrowing of left MCA and non-visualization of distal part. There is extensive fine collaterals (Moyamoya vessels) giving the appearance of puffed smoke. The right ACA and MCA were also narrowed with appearance of early collateral vessels. She was treated with aspirin, PPI, NG feeding, antihypertensive medication, physiotherapy, rehabilitation therapy and other supportive care. His condition gradually improved and discharged on 2.7.19. He was referred to Department of Neurosurgery for cerebral revascularization by STA-MCA (superficial temporal and middle cerebral arteries) bypass surgery after stabilization and MR perfusion study. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 110-113